The Impact of War Experiences in Europe The Conscription of Non-German Men and Women into the ‘Wehrmacht’ and ‘Reichsarbeitsdienst’ (1938–1945) - Beck, Philippe; Echternkamp, Jörg; Ganschow, Inna; Geny, Philippe; Graczyk, Konrad; Janz, Nina 1986-; Kocjancic, Klemen; Kokalj Kočevar, Monika; Kossytorz, Tobias; Scuto, Denis 1964-; Streicher, Félix; Venken, Machteld; et al. (Studien zur transnationalen Zeitgeschichte Luxemburgs, 2024)
During World War II, over half a million men and women under Nazi occupation, who lacked German citizenship, were forcibly conscripted into the German Reichsarbeitsdienst and the Wehrmacht. The Nazis sought to legitimize this conscription by labeling these individuals as “deutsche Volkszugehörige” or “Deutschstämmige,” despite it being a clear violation of international law.This collection explores the lives of these non-German conscripts, focusing on individuals from Slovenia, Poland (Silesia), Luxembourg, Belgium, and France. Each chapter adopts an actor-centered approach, examining their daily lives, social dynamics, recruitment, military deployment, and experiences in German uniform under coercion.The authors cover cases of desertion and escapes to neutral countries, along with the repercussions for families, tracing the capture of conscripts as POWs and the complex processes of redeployment by the Allies against the Germans and the re-conscription by national governments. Through a rich collection of ego documents and personal records, this work vividly captures their complex realities, offering nuanced insights into the dynamics of occupation, coercion, and the shifting allegiances that defined wartime and post-war Europe.